Insurance customer behavior: Lessons from behavioral economics. Issue 2 (25th July 2019) - Richter, Andreas; Ruß, Jochen; Schelling, Stefan
Abstract: In economics it has traditionally been assumed that people make all their decisions like the so‐called homo oeconomicus – that is, maximizing (expected) utility of total wealth. In recent years, economics increasingly recognized that people often exhibit behavioral patterns which are incompatible with the idea of the homo oeconomicus. The field of behavioral economics incorporates insights from the field of psychology to explain discrepancies between predictions of traditional economic theory and actual observed behavior. In this paper, we summarize a selection of well‐established behavioral patterns observed in reality and discuss their relevance for the insurance industry when it comes to better understanding and predicting customer behavior. We also explain that people are not always risk‐averse and give a brief overview over Prospect Theory (probably the most popular behavioral economics alternative to Expected Utility Theory), its shortcomings for predicting behavior over a long time horizon, and its extensions. In total, we point out that, since dealing with risks and insurance products requires complex decision making processes, a deep understanding of the impacts of behavioral factors is essential to better assess and explain costumer behavior.